Psikoedukasi Self-Disclosure and Trust Dalam Industri Perhotelan - Rahmawati Syam; Syamsul Bakhri Gaffar; Dhede Tazkiya Octsananda Ramli; Siti Adriyanti; Siti Hajrahwaty; Tiara Angreni; Mustika Kusuma (AMMA : Jurnal Pengabdian Masyarakat, 2023)
Interpersonal communication is communication that occurs face-to-face with individuals that allows each individual to capture the reactions of other individuals directly verbally and non-verbally in their environment. As social beings, humans always establish relationships with other individuals that cannot be separated from everyday life. In order for the relationship between individuals to work harmoniously, adjustment is needed and requires communication. Employees are individuals who do a lot of work that is very decisive and meaningful for the organization. The method used is psychoeducation in the form of seminar activities that aim to provide information and training that is useful in changing an individual's mental or psychological understanding. Psychoeducation is an activity carried out to increase the understanding of skills as an effort to prevent the emergence or spread of psychological disorders in a group. This activity is carried out offline in the form of seminar activities by presenting experts as the main resource persons. This activity was carried out attractively in the form of seminar activities by presenting experts as the main sources. This psychoeducation seminar was held on May 17 2023 with 22 participants. Through this activity, Gammara Hotel Makassar employees gain knowledge about what is meant by verbal and nonverbal interpersonal communication and what aspects are needed to realize the implementation of good communication in self-disclosure and trust between colleagues.